Yüzyılın sorunları ve sosyoloji - Açıköz, H. Mustafa; Toku, Neşet; Doğan, Mehmet; Tezgel, Recep; Karslı, Temel Alper; Durdu, Zafer; Yılmaz, Sinan; Yücer, Hür Mahmut; Öztürk, Ali (Bartın Üniversitesi, 2015)
[Abstract Not Available]
Keywords: Sosyoloji; Sociology